Anti-crack flame-retardant double-sided glass fiber adhesive tape and preparation method thereof

Through the chemical cross-linking of polyepoxy cashew phenol-based flame retardant with end carboxylic nitrile rubber and light calcium carbonate filling, the flammability and high-temperature cracking of glass fiber tape is solved, and the crack resistance and flame retardant performance is improved. Optimization of bonding performance has expanded its application scope.

CN119193032AInactive Publication Date: 2024-12-27JIANGSU AOKAI NEW MATERIAL TECH CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411466918.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-05-28
Publication Date
2024-12-27
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing fiberglass tape is flammable during fire, has poor flame retardant performance, and is prone to cracking under high temperature conditions, which limits its application range.

Method used

Chemical crosslinking is performed with polyepoxy cashew phenol-based flame retardant and end carboxylic nitrile rubber and bisphenol A epoxy resin to form a dense three-dimensional network structure, and light calcium carbonate and other fillers are added to prepare crack resistance resistance Burn double-sided fiberglass tape.

Benefits of technology

It improves the flame retardant and crack resistance of glass fiber tape, extends the service life of adhesive performance, reduces fire safety risks, and broadens its application range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005093624410000031
    Figure BDA0005093624410000031
  • Figure BDA0005093624410000032
    Figure BDA0005093624410000032
  • Figure BDA0005093624410000091
    Figure BDA0005093624410000091
Patent Text Reader

Abstract

The invention relates to the technical field of adhesive tapes, and discloses an anti-crack flame-retardant double-sided glass fiber adhesive tape and a preparation method thereof, phosphoric acid compounds generated in the heating or combustion process of an epoxy cardanol-based flame retardant promote dehydration of an adhesive tape matrix to form a protective carbon layer, reduce heat release in the combustion process and improve the fire safety of the adhesive tape; epoxy groups in the structure can react with carboxyl-terminated nitrile rubber, so that the dispersity in epoxy resin is more uniform, a three-dimensional network structure with certain crosslinking density is formed, migration and precipitation are not easy to occur, and the flame-retardant durability is better; the polyepoxy cardanol-based flame retardant has good compatibility with the epoxy resin, and the linear flexible alkyl long chain has good toughness, so that when the adhesive tape is cracked by external force, part of energy can be absorbed to disperse stress and reduce brittleness, and an adhesive tape matrix is endowed with better impact resistance, thereby improving the crack resistance of the adhesive tape.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application with the application date of May 28, 2024, application number 202410670358.9, and the invention name is "A crack-resistant flame-retardant double-sided glass fiber tape and its preparation method." Technical Field

[0002] The invention relates to the technical field of adhesive tapes, in particular to a crack-resistant and flame-retardant double-sided glass fiber adhesive tape and a preparation method thereof. Background Art

[0003] Fiberglass double-sided tape is a tape made of glass fiber cloth as the base layer. It is a self-adhesive tape with high strength, excellent sealing performance, adhesion and chemical resistance. It is often used for interlayer insulation and bundling of high-frequency inverters and microwave oven transformers, bundling and fixing of metal strips, and winding and fixing of quartz tubes. However, in the production and application of fiberglass tape, the improvement of flame retardant properties is still a problem that needs to be solved urgently. Conventional fiberglass tape is flammable and easily produces molten droplets and causes the fire to spread in the event of a fire, causing serious harm to human life and property safety, greatly limiting the application scope of fiberglass tape. Although studies have been conducted on the flame retardant modification of fiberglass tape, there are still certain limitations, such as unsatisfactory flame retardant effect and low efficiency.

[0004] High-performance fiberglass tape is mainly suitable for sealing tape. At present, many hot-melt pressure-sensitive adhesive products on the market have reduced bonding performance after heat aging treatment, and the glass fiber in the fiberglass tape is easily compatible with the oil component of the hot-melt adhesive under high temperature conditions, resulting in reduced tensile strength of the tape itself, easy cracking, and reduced applicability. Therefore, it is necessary to prepare a flame-retardant and crack-resistant double-sided fiberglass tape based on the existing technology, which has become an urgent problem to be solved.

[0005] Epoxy resin adhesive is known as "all-purpose glue", and carboxyl nitrile rubber has good adhesion and aging resistance. The combination of the two and other components can be used as the main component of glass fiber tape, but the limiting oxygen index of epoxy resin and carboxyl nitrile rubber is relatively low. In the prior art, inorganic flame retardants such as magnesium hydroxide, aluminum hydroxide, etc. are generally added to play a flame retardant role to a certain extent, but the amount added is large and agglomeration is prone to occur, which further affects the viscosity and effect of the adhesive; the present invention aims to synthesize a flexible epoxy flame retardant, which has structural similarities with epoxy resin, can be chemically cross-linked with carboxyl nitrile rubber to form a dense cross-linked network structure, and light calcium carbonate and the like are added as fillers to obtain a double-sided glass fiber tape with both flame retardant and crack resistance, good bonding performance, and broaden the application range of the glass fiber tape. Summary of the invention

[0006] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a crack-resistant flame-retardant double-sided glass fiber tape and a preparation method thereof, thereby solving the problem that the existing double-sided glass fiber tape has poor flame retardant performance and is easy to crack.

[0007] To achieve the above object, the technical solution adopted by the present invention is:

[0008] A crack-resistant flame-retardant double-sided glass fiber tape comprises a substrate and an adhesive coated on the upper and lower surfaces of the substrate.

[0009] The substrate is glass fiber cloth treated with low-temperature plasma.

[0010] The adhesive comprises 100 parts by weight of carboxyl-terminated nitrile rubber, 35-50 parts by weight of bisphenol A epoxy resin, 3-8 parts by weight of terpene resin, 2-10 parts by weight of polyepoxy cardanol-based flame retardant, 5-12 parts by weight of filler, 2-4 parts by weight of antioxidant and 1-3 parts by weight of dimethyl silicone oil.

[0011] The preparation method of the adhesive is as follows: add terminal carboxyl nitrile rubber, bisphenol A epoxy resin and dimethyl silicone oil into a high-speed mixer, stir evenly at a speed of 1000-1500r / min and a temperature of 80-100°C, add a polyepoxy cardanol-based flame retardant, a filler and a terpene resin, stir for 1-3h, add an antioxidant, continue stirring for 20-40min, cool and extrude to obtain the adhesive.

[0012] Preferably, the filler is any one of light calcium carbonate, talcum powder or seaweed powder.

[0013] Preferably, the antioxidant is any one of N-phenyl-2-naphthylamine, 4,4-di-tert-octyldiphenylamine or N,N-diphenyl-p-phenylenediamine.

[0014] Preferably, the preparation method of the polyepoxy cardanol-based flame retardant is:

[0015] (1) In a nitrogen atmosphere, add cardanol and acetone to a reaction flask, stir evenly, add hexachlorocyclotriphosphazene and cesium carbonate, stir and react, and after the reaction is completed, cool to room temperature, extract with ethyl acetate and deionized water, concentrate the organic phase, and dry to obtain a polyphenylphosphinothioate cardanol intermediate. The preparation reaction formula is as follows:

[0016]

[0017] (2) In a nitrogen atmosphere, add polyphenylphosphinothioic acid cardanol intermediate and dichloromethane to a reaction flask, stir evenly, add m-chloroperbenzoic acid, react at 20-35° C. for 3-8 hours, filter, wash the filtrate with sodium carbonate solution and deionized water, concentrate, and dry to obtain a polyepoxy cardanol-based flame retardant. The preparation reaction formula is as follows:

[0018]

[0019] Preferably, in step (1), the ratio of cardanol, hexachlorocyclotriphosphazene and cesium carbonate is (6.5-8) mol:1 mol:(8.5-10) mol.

[0020] Preferably, in step (1), the reaction temperature is 55-70° C. and the reaction time is 16-24 h.

[0021] Preferably, in step (2), the ratio of the polyphenylphosphazene cardanol intermediate to meta-chloroperbenzoic acid is 1 mol:(7.5-9) mol.

[0022] Preferably, the mass fraction of the sodium carbonate solution in step (2) is 10-20%.

[0023] Preferably, the preparation method is: placing a glass fiber cloth substrate on a coating machine, passing through a reel, a pressure roller, and a reel and keeping it in a horizontal state, and evenly applying the prepared adhesive on the upper and lower surfaces of the substrate through a coating roller, with a thickness of the adhesive layer of 0.15-0.25 mm, and then placing it in an oven for drying and curing, attaching a release film and then winding it up to obtain a crack-resistant and flame-retardant double-sided glass fiber tape.

[0024] Preferably, the drying and curing temperature is 120-140° C., and the drying and curing time is 2-5 hours.

[0025] By adopting the above technical solution, the beneficial effects of the present invention are:

[0026] The invention firstly reacts cardanol with hexachlorocyclotriphosphazene under the action of cesium carbonate to obtain a polyphenylcyclophosphonitrile cardanol intermediate, then adds meta-chloroperbenzoic acid to cause an olefin epoxidation reaction to obtain a polyepoxy cardanol-based flame retardant, then mixes the mixture evenly with carboxyl-terminated nitrile rubber, bisphenol A epoxy resin and the like to obtain an adhesive, and finally evenly coats the mixture on a glass fiber cloth treated with low-temperature plasma to obtain a crack-resistant flame-retardant double-sided glass fiber tape.

[0027] During the heating or combustion process, the epoxy cardanol-based flame retardant will degrade in advance to produce phosphoric acid compounds, which will promote the dehydration of the tape matrix to form a protective carbon layer. The formed carbon layer can effectively block the heat and mass transfer between the internal matrix and the combustion area, thereby inhibiting the spread of fire, reducing the heat release during the combustion process, and improving its own fire safety; at the same time, the polyepoxy cardanol-based flame retardant contains six cardanol groups, among which the epoxy groups can react with the carboxyl-terminated nitrile rubber, and the dispersion in the epoxy resin is more uniform, forming a three-dimensional network structure with a certain cross-linking density, so that the flame retardant is stably present in the resin matrix, is not easy to migrate and precipitate, and has good flame retardant and durable performance.

[0028] The polyepoxy cardanol-based flame retardant has multiple epoxy groups, can be chemically cross-linked with terminal carboxyl nitrile rubber to form a dense three-dimensional cross-linked network structure, and has good compatibility with epoxy resin, thereby improving the dispersibility of the tape matrix and increasing the tensile strength; in addition, the linear flexible alkyl long chain of cardanol has good toughness, and when the tape is cracked by external force, it can absorb part of the energy to disperse the stress, reduce brittleness, and give the tape matrix better impact resistance, thereby improving the anti-cracking performance of the tape; cardanol is extracted from natural cashew nut shell oil, which is abundant in source, low in price and renewable. The double-sided glass fiber tape prepared by the present invention not only has anti-cracking flame retardant performance, but also has excellent bonding performance, is green and environmentally friendly, and has a wide range of applications. DETAILED DESCRIPTION

[0029] The technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] Cardanol: Provided by Cardolite (Zhuhai, China), light yellow liquid, composed of 41% triene, 36% diene, and 23% monoene, with the structural formula

[0031] Hexachlorocyclotriphosphazene, CAS number is 940-71-6.

[0032] Meta-chloroperbenzoic acid, CAS number is 937-14-4.

[0033] Example 1

[0034] (1) Under nitrogen atmosphere, 105 mmol of cardanol and 180 mL of acetone were added to a reaction flask, and after stirring, 15 mmol of hexachlorocyclotriphosphazene and 135 mmol of cesium carbonate were added, and the mixture was reacted at 65° C. for 18 h. The mixture was cooled to room temperature, extracted with ethyl acetate and deionized water, and the organic phase was concentrated and dried to obtain a polyphenylphosphinothioic acid cardanol intermediate.

[0035] (2) Under a nitrogen atmosphere, 12 mmol of a polyphenylphosphinothioic acid cardanol intermediate and 660 mL of dichloromethane were added to a reaction flask, stirred evenly, and then 102 mmol of m-chloroperbenzoic acid was added. The mixture was reacted at 25 °C for 5 h, filtered, and the filtrate was washed with a 15% sodium carbonate solution and deionized water, concentrated, and dried to obtain a polyepoxy cardanol-based flame retardant.

[0036] (3) 100 g of carboxyl-terminated nitrile rubber, 45 g of bisphenol A epoxy resin and 2 g of dimethyl silicone oil were added to a high-speed mixer and stirred at a speed of 1200 r / min and a temperature of 90°C. 2 g of polyepoxy cardanol-based flame retardant, 6 g of light calcium carbonate and 5 g of terpene resin were added and stirred for 2 h. 3 g of N-phenyl-2-naphthylamine was added and stirred for 30 min. The mixture was cooled and extruded to obtain an adhesive.

[0037] (4) The glass fiber cloth substrate treated with low-temperature plasma is placed on a coating machine, and the prepared adhesive is evenly applied to the upper and lower surfaces of the substrate through a coating roller through a reel, a pressure roller, and a reel and kept in a horizontal state. The thickness of the adhesive layer is 0.2 mm, and then placed in an oven at room temperature of 130°C for drying and curing for 4 hours. After attaching a release film, it is rolled up to obtain a crack-resistant flame-retardant double-sided glass fiber tape.

[0038] Example 2

[0039] (1) Under a nitrogen atmosphere, 260 mmol of cardanol and 400 mL of acetone were added to a reaction flask. After stirring, 40 mmol of hexachlorocyclotriphosphazene and 340 mmol of cesium carbonate were added. The mixture was reacted at 70° C. for 16 h. The mixture was cooled to room temperature, extracted with ethyl acetate and deionized water, and the organic phase was concentrated and dried to obtain a polyphenylphosphinothioate cardanol intermediate.

[0040] (2) Under a nitrogen atmosphere, 35 mmol of a polyphenylphosphinothioic acid cardanol intermediate and 1750 mL of dichloromethane were added to a reaction flask, stirred evenly, and then 262.5 mmol of m-chloroperbenzoic acid was added. The mixture was reacted at 35 °C for 3 h, filtered, and the filtrate was washed with a 10% sodium carbonate solution and deionized water, concentrated, and dried to obtain a polyepoxy cardanol-based flame retardant.

[0041] (3) Add 100 g of terminal carboxyl nitrile rubber, 35 g of bisphenol A epoxy resin and 3 g of dimethyl silicone oil into a high-speed mixer and stir evenly at a speed of 1500 r / min and a temperature of 100°C. Add 4 g of polyepoxy cardanol-based flame retardant, 12 g of talc and 8 g of terpene resin and stir for 1 h. Add 2 g of 4,4-di-tert-octyl diphenylamine and continue stirring for 20 min. Cool and extrude to obtain an adhesive.

[0042] (4) The glass fiber cloth substrate treated with low-temperature plasma is placed on a coating machine, and the prepared adhesive is evenly applied to the upper and lower surfaces of the substrate through a coating roller through a reel, a pressure roller, and a reel, and kept in a horizontal state. The thickness of the adhesive layer is 0.15 mm, and then placed in an oven at room temperature of 140°C for drying and curing for 2 hours. After attaching a release film, it is rolled up to obtain a crack-resistant flame-retardant double-sided glass fiber tape.

[0043] Example 3

[0044] (1) Under nitrogen atmosphere, 80 mmol of cardanol and 150 mL of acetone were added to a reaction flask, and after stirring, 10 mmol of hexachlorocyclotriphosphazene and 100 mmol of cesium carbonate were added, and the mixture was reacted at 55 °C for 24 h. The mixture was cooled to room temperature, extracted with ethyl acetate and deionized water, and the organic phase was concentrated and dried to obtain a polyphenylphosphinothioic acid cardanol intermediate.

[0045] (2) Under a nitrogen atmosphere, 8 mmol of polyphenylphosphinothioic acid cardanol intermediate and 480 mL of dichloromethane were added to a reaction flask, stirred evenly, and then 72 mmol of m-chloroperbenzoic acid was added. The mixture was reacted at 20° C. for 8 h, filtered, and the filtrate was washed with a 20% sodium carbonate solution and deionized water, concentrated, and dried to obtain a polyepoxy cardanol-based flame retardant.

[0046] (3) Add 100 g of terminal carboxyl nitrile rubber, 50 g of bisphenol A epoxy resin and 1 g of dimethyl silicone oil into a high-speed mixer and stir evenly at a speed of 1000 r / min and a temperature of 80°C. Add 6 g of polyepoxy cardanol-based flame retardant, 5 g of seaweed powder and 8 g of terpene resin and stir for 3 h. Add 4 g of N,N-diphenyl-p-phenylenediamine and continue stirring for 40 min. Cool and extrude to obtain an adhesive.

[0047] (4) The glass fiber cloth substrate treated with low-temperature plasma is placed on a coating machine, and the prepared adhesive is evenly applied to the upper and lower surfaces of the substrate through a coating roller through a reel, a pressure roller, and a reel and kept in a horizontal state. The thickness of the adhesive layer is 0.25 mm, and then placed in an oven at room temperature of 120°C for drying and curing for 5 hours. After attaching a release film, it is rolled up to obtain a crack-resistant flame-retardant double-sided glass fiber tape.

[0048] Example 4

[0049] (1) Under nitrogen atmosphere, 180 mmol of cardanol and 325 mL of acetone were added to a reaction flask, and after stirring, 25 mmol of hexachlorocyclotriphosphazene and 220 mmol of cesium carbonate were added, and the mixture was reacted at 60° C. for 22 h. The mixture was cooled to room temperature, extracted with ethyl acetate and deionized water, and the organic phase was concentrated and dried to obtain a polyphenylphosphinothioic acid cardanol intermediate.

[0050] (2) Under a nitrogen atmosphere, 18 mmol of a polyphenylphosphinothioic acid cardanol intermediate and 990 mL of dichloromethane were added to a reaction flask, stirred evenly, and then 155 mmol of m-chloroperbenzoic acid was added. The mixture was reacted at 30° C. for 8 h, filtered, and the filtrate was washed with a 15% sodium carbonate solution and deionized water, concentrated, and dried to obtain a polyepoxy cardanol-based flame retardant.

[0051] (3) 100 g of carboxyl-terminated nitrile rubber, 40 g of bisphenol A epoxy resin and 2.5 g of dimethyl silicone oil were added to a high-speed mixer and stirred at a speed of 1450 r / min and a temperature of 95°C. 8 g of polyepoxy cardanol-based flame retardant, 10 g of light calcium carbonate and 6 g of terpene resin were added and stirred for 3 h. 3.5 g of N-phenyl-2-naphthylamine was added and stirred for 30 min. The mixture was cooled and extruded to obtain an adhesive.

[0052] (4) The glass fiber cloth substrate treated with low-temperature plasma is placed on a coating machine, and the prepared adhesive is evenly applied to the upper and lower surfaces of the substrate through a coating roller through a reel, a pressure roller, and a reel and kept in a horizontal state. The thickness of the adhesive layer is 0.2 mm, and then placed in an oven at room temperature of 135°C for drying and curing for 4 hours. After attaching a release film, it is rolled up to obtain a crack-resistant flame-retardant double-sided glass fiber tape.

[0053] Example 5

[0054] (1) Under nitrogen atmosphere, 135 mmol of cardanol and 200 mL of acetone were added to a reaction flask. After stirring, 18 mmol of hexachlorocyclotriphosphazene and 160 mmol of cesium carbonate were added. The mixture was reacted at 70 °C for 24 h. The mixture was cooled to room temperature, extracted with ethyl acetate and deionized water, and the organic phase was concentrated and dried to obtain a polyphenylphosphinothioate cardanol intermediate.

[0055] (2) Under a nitrogen atmosphere, 15 mmol of a polyphenylphosphinothioic acid cardanol intermediate and 825 mL of dichloromethane were added to a reaction flask, stirred evenly, and then 130 mmol of m-chloroperbenzoic acid was added. The mixture was reacted at 35 °C for 8 h, filtered, and the filtrate was washed with a 10% sodium carbonate solution and deionized water, concentrated, and dried to obtain a polyepoxy cardanol-based flame retardant.

[0056] (3) 100 g of carboxyl-terminated nitrile rubber, 50 g of bisphenol A epoxy resin and 3 g of dimethyl silicone oil were added to a high-speed mixer and stirred at a speed of 1500 r / min and a temperature of 90°C. 10 g of a polyepoxy cardanol-based flame retardant, 6 g of talc and 5 g of a terpene resin were added and stirred for 3 h. 4 g of 4,4-di-tert-octyl diphenylamine was added and stirred for 35 min. The mixture was cooled and extruded to obtain an adhesive.

[0057] (4) The glass fiber cloth substrate treated with low-temperature plasma is placed on a coating machine, and the prepared adhesive is evenly applied to the upper and lower surfaces of the substrate through a coating roller through a reel, a pressure roller, and a reel and kept in a horizontal state. The thickness of the adhesive layer is 0.2 mm, and then placed in an oven at room temperature of 125°C for drying and curing for 5 hours. After attaching a release film, it is rolled up to obtain a crack-resistant flame-retardant double-sided glass fiber tape.

[0058] Comparative Example 1

[0059] (1) 100 g of nitrile rubber, 45 g of bisphenol A epoxy resin and 2 g of dimethyl silicone oil were added to a high-speed mixer and stirred at a speed of 1200 r / min and a temperature of 90° C. 2 g of a polyepoxy cardanol-based flame retardant (prepared in Example 1), 6 g of light calcium carbonate and 5 g of a terpene resin were added and stirred for 2 h. 3 g of N-phenyl-2-naphthylamine was added and stirred for 30 min. The mixture was cooled and extruded to obtain an adhesive.

[0060] (2) The glass fiber cloth substrate treated with low-temperature plasma is placed on a coating machine, and the prepared adhesive is evenly applied to the upper and lower surfaces of the substrate through a coating roller through a reel, a pressure roller, and a reel and kept in a horizontal state. The thickness of the adhesive layer is 0.2 mm, and then placed in an oven at room temperature of 130° C. for drying and curing for 4 hours. After attaching a release film, it is rolled up to obtain a double-sided glass fiber tape.

[0061] Comparative Example 2

[0062] (1) 100 g of carboxyl-terminated nitrile rubber, 45 g of bisphenol A epoxy resin and 2 g of dimethyl silicone oil were added to a high-speed mixer and stirred at a speed of 1200 r / min and a temperature of 90° C. 6 g of light calcium carbonate and 5 g of terpene resin were added and stirred for 2 h. 3 g of N-phenyl-2-naphthylamine was added and stirred for 30 min. The mixture was cooled and extruded to obtain an adhesive.

[0063] (2) The glass fiber cloth substrate treated with low-temperature plasma is placed on a coating machine, and the prepared adhesive is evenly applied to the upper and lower surfaces of the substrate through a coating roller through a reel, a pressure roller, and a reel and kept in a horizontal state. The thickness of the adhesive layer is 0.2 mm, and then placed in an oven at room temperature of 130° C. for drying and curing for 4 hours. After attaching a release film, it is rolled up to obtain a double-sided glass fiber tape.

[0064] Limiting oxygen index test (LOI): Referring to ASTM D2863-1993 standard, the limiting oxygen index instrument is used for testing, and the sample size is 100mm×6.5mm×3.2mm.

[0065] Vertical burning test (UL-94): Refer to ASTM D3810-1996 standard, use vertical burning tester for testing, the sample size is 100mm×13mm×3.2mm.

[0066] Table 1 Flame retardant performance test

[0067]

[0068]

[0069] It can be seen from the test results in the above table that with the increase of the content of the polyepoxy cardanol-based flame retardant, the flame retardant properties of the double-sided glass fiber tape are gradually enhanced. The limiting oxygen index in Example 5 reaches 31.8%, and the vertical combustion grade is V-0, which belongs to the level of flame-retardant materials. This is because the polyepoxy cardanol-based flame retardant will degrade in advance to produce phosphoric acid compounds during heating or combustion, thereby promoting the dehydration of the tape matrix to form a protective carbon layer. The formed carbon layer can effectively block the heat and mass transfer between the internal matrix and the combustion area, thereby inhibiting the spread of fire, reducing the heat release during the combustion process, and improving its own fire safety; at the same time, the polyepoxy cardanol-based flame retardant contains six cardanol groups, the epoxy groups of which can react with the carboxyl-terminated nitrile rubber to form a three-dimensional network structure with a certain cross-linking density, so that the flame retardant is stably present in the resin matrix, not easy to migrate and precipitate, and has good flame retardant and durable performance.

[0070] In Comparative Example 1, nitrile rubber is used instead of terminal carboxyl nitrile rubber, which cannot produce chemical crosslinking with bisphenol A epoxy resin and polyepoxy cardanol-based flame retardant, but contains flame retardant and has a certain flame retardant effect; Comparative Example 2 does not contain flame retardant and has no flame retardant effect.

[0071] Impact strength test: refer to GB / T 1043.1-2008 standard, use pendulum impact tester for testing, impact energy is 5J, sample size is 80mm×10mm×4mm.

[0072] Tensile strength test: refer to GB / T 30776-2014 standard, use universal electronic tensile testing machine for testing, the tensile rate is 10mm / min.

[0073] Table 2 Mechanical properties test

[0074]

[0075]

[0076] It can be seen from the test results in the above table that with the increase of the content of the polyepoxy cardanol-based flame retardant, the mechanical properties of the double-sided glass fiber tape are gradually enhanced. The impact strength in Example 4 is 21.62 kJ / m 2, the tensile strength is 60.85MPa, which shows that the polyepoxy cardanol-based flame retardant has a toughening effect on the double-sided glass fiber tape. This is because, on the one hand, the polyepoxy cardanol-based flame retardant has multiple epoxy groups, which can be chemically cross-linked with the carboxyl-terminated nitrile rubber to form a dense three-dimensional cross-linked network structure, and at the same time has good compatibility with epoxy resin, which improves the dispersibility of the tape matrix and increases the tensile strength; on the other hand, the linear flexible alkyl long chain of cardanol has good toughness. When the tape is cracked by external force, it can absorb part of the energy to disperse the stress, reduce brittleness, and give the tape matrix better impact resistance, thereby improving the crack resistance of the tape.

[0077] 180° peel strength test: Refer to GB / T 2792-2014 standard and use peel strength tensile tester for testing.

[0078] Tear strength test: Tested in accordance with GB / T 36878-2018 standard.

[0079] Table 3 Tape performance test

[0080]

[0081]

[0082] Obviously, the specific implementation of the present invention is not limited to the above-mentioned methods. As long as various non-substantial improvements are made using the method concept and technical solution of the present invention, or the concept and technical solution of the present invention are directly applied to other occasions without improvement, they are all within the protection scope of the present invention.

Claims

1. A crack-resistant flame-retardant double-sided glass fiber tape, characterized in that: The double-sided glass fiber tape comprises a substrate and an adhesive coated on the upper and lower surfaces of the substrate; The substrate is a glass fiber cloth treated with low-temperature plasma; The adhesive comprises 100 parts by weight of carboxyl-terminated nitrile rubber, 35-50 parts by weight of bisphenol A epoxy resin, 3-8 parts by weight of terpene resin, 2-10 parts by weight of polyepoxy cardanol-based flame retardant, 5-12 parts by weight of filler, 2-4 parts by weight of antioxidant and 1-3 parts by weight of dimethyl silicone oil; The preparation method of the adhesive is as follows: add carboxyl-terminated nitrile rubber, bisphenol A epoxy resin and dimethyl silicone oil into a high-speed mixer, stir evenly at a speed of 1000-1500 r / min and a temperature of 80-100° C., add a polyepoxy cardanol-based flame retardant, a filler and a terpene resin, stir for 1-3 hours, add an antioxidant, continue stirring for 20-40 minutes, cool and extrude to obtain the adhesive; The preparation method of the polyepoxy cardanol-based flame retardant is: (1) Under a nitrogen atmosphere, add cardanol and acetone to a reaction flask, stir evenly, add hexachlorocyclotriphosphazene and cesium carbonate, stir and react, and after the reaction is completed, cool to room temperature, extract with ethyl acetate and deionized water, concentrate the organic phase, and dry to obtain a polyphenylphosphinothioate cardanol intermediate; In the step (1), the ratio of cardanol, hexachlorocyclotriphosphazene and cesium carbonate is (6.5-8) mol: 1 mol: (8.5-10) mol; (2) Under a nitrogen atmosphere, add a polyphenylphosphinothioate cardanol intermediate and dichloromethane to a reaction flask, stir evenly, add m-chloroperbenzoic acid, react at 20-35° C. for 3-8 h, filter, wash the filtrate with sodium carbonate solution and deionized water, concentrate, and dry to obtain a polyepoxy cardanol-based flame retardant; In the step (2), the ratio of the polyphenylphosphanitrocardanol intermediate to m-chloroperbenzoic acid is 1 mol: (7.5-9) mol; The preparation method of the anti-cracking flame-retardant double-sided glass fiber tape is as follows: a glass fiber cloth substrate is placed on a coating machine, and the prepared adhesive is evenly applied to the upper and lower surfaces of the substrate through a coating roller through a reel, a pressure roller, and a reel and kept in a horizontal state, and the thickness of the adhesive layer is 0.15-0.25 mm, and then placed in an oven for drying and curing, and a release film is attached and then rolled up to obtain the anti-cracking flame-retardant double-sided glass fiber tape; The drying and curing temperature is 120-140° C., and the drying and curing time is 2-5 hours.

2. The anti-cracking flame-retardant double-sided glass fiber tape according to claim 1, characterized in that: The filler is any one of light calcium carbonate, talcum powder or seaweed powder.

3. The crack-resistant flame-retardant double-sided glass fiber tape according to claim 1, characterized in that: The antioxidant is any one of N-phenyl-2-naphthylamine, 4,4-di-tert-octyl diphenylamine or N,N-diphenyl-p-phenylenediamine.

4. The crack-resistant flame-retardant double-sided glass fiber tape according to claim 1, characterized in that: In the step (1), the reaction temperature is 55-70° C. and the reaction time is 16-24 h.

5. The crack-resistant flame-retardant double-sided fiberglass tape according to claim 1, characterized in that: The mass fraction of the sodium carbonate solution in step (2) is 10-20%.

Citation Information

Cited By

  • High-bonding-strength flame-retardant composite foam board and preparation method thereof

    CN119858374A

  • Epoxy resin adhesive with high bio-based content and intrinsic flame retardance and preparation method thereof

    CN121160264A